Mechanisms of trypanosome-mediated suppression of humoral immunity in mice - Albright, Julia W. (1978)
Spleen cells from Trypanosoma musculi-infected mice were unable to respond to sheep erythrocyte antigen in vitro; moreover, they suppressed the responses of normal spleen cell cultures in dose-dependent fashion. Suppression was maximal with spleen cells obtained during maximal parasitemia and waned as the donors recovered from infection. A macrophage-enriched population of spleen cells from infected mice, prepared either by adherence to plastic or by density gradient centrifugation, was not contaminated by the parasites and was not suppressive, whereas the plastic-nonadherent population was both contaminated and suppressive. Adherent and nonadherent cells of infected mice, separated by use of nylon wool columns, were almost equally suppressive and equally contaminated by trypanosomes. Addition of specific rabbit antiserum against T. musculi to cultures containing cells from infected mice eliminated contaminating parasites and alleviated suppression exerted by cells obtained from mice early during the course of infection but not after 12-15 days of infection. The suppression exerted by enriched T-cells obtained from mice on day 12 of infection was largely alleviated by use of the antiserum. A large portion of cells obtained on day 14 of infection could be killed by the antiserum and complement. It appeared that soluble substances derived from the parasites acted directly on B lymphocytes or essential assistant cells rather than by activating suppressor T cells or macrophages.